Sosialisasi Anti Tawuran Oleh Mahasiswa Kkn Bersama Kepolisian Di SDN Mekarsari 01 - Sherliane Vanesa; Pasha Shabrina; Al Fadhli (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
To examine the implementation of anti-fighting counseling conducted by students participating in the Community Service Program (KKN) in collaboration with the police at SDN Mekarsari 01 as an effort to prevent fighting among students from an early age. The methods used consisted of training students by supervising lecturers, field research through surveys and observations, and interactive counseling that included discussions, educational games, and presentations from police representatives. The evaluation of the results of the socialization was carried out by collecting the opinions of students and teachers. The research findings show that the presence of police representatives as resource persons had a positive impact on students' understanding of the dangers of gang fighting, the legal consequences, and the importance of resolving conflicts peacefully. The active involvement of students, the support of teachers as mentors, and the application of interactive methods played an important role in instilling anti-violence values. This program successfully created collaboration between KKN students, schools, and the police to build a safe, orderly, and harmonious school environment. It is recommended that similar activities be carried out continuously with the development of more innovative methods and increased parental involvement to support the formation of positive character in students.